Towards drop your thesis 2018: 4.7 seconds of microgravity conditions to enable future CubeSat landings on asteroids - Sánchez Cuartielles, Joan Pau; Sitepu, Elioenai; Le Blay, Carole; Kersey, George; Ogborne, Stuart; Durrani, Daniyal Ahmad; Zanotti Fragonara, Luca; Gautier, Florian; Kingston, Jennifer (International Astronautical Federation (IAF), 2018)
An increasing number of interplanetary missions are aiming at visiting asteroids and other small bodies, since these may provide clues to understand the formation and evolution of our Solar System. CubeSats allow a low-cost solution to land on these objects, as opposed to risking a much more expensive mothership. The weak gravitational field on these small bodies may also enable the possibility of simply dropping a CubeSat from afar (i.e. ballistic landing). However, ballistic landing of an unpowered spacecraft may be feasible solely within certain asteroid locations, and only if sufficient energy can be dissipated at touchdown. If such conditions are not met, the spacecraft will rebound off the surface. It is likely that the necessary energy dissipation may already occur naturally due to energy loss expected through the deformation of the regolith during touchdown. Indeed, previous low-velocity impact experiments in microgravity seem to indicate that this is exactly the case. However, data from past asteroid touchdowns, Hayabusa and Philae, indicate the contrary. This paper describes the development of an experiment which aims to bridge the aforementioned disagreement between mission data and microgravity experiment; to understand the behaviour of CubeSat landing on asteroids. The experiment will also test a novel damping system made by origami paper that should increase the dissipated energy at touchdown. The experiment will take place at the ZARM Drop Tower in Bremen in November 2018. With the constraint of 5 drops, the experiment will measure the coefficient of restitution during an available time window of 4.74 seconds of microgravity conditions. A 1UCubeSat mock-up will be used to represent a future asteroid lander. In order to mimic the landing of actual missions, the mock-up will have a mass of about 4 kg and it will be given a velocity of 15 cm/s with minimal rotation. This will be achieved by an automated spring-based release mechanism. An asteroid simulant, ESA03-A KM Bentonite Granules will be used to replicate an asteroid mechanical properties at the surface. This paper reviews the final design and the engineering challenges of the experiment.
Keywords: Coefficient of Restitution; CubeSat Landing; Asteroid; Microgravity; Drop Your Thesis; ZARM drop tower